Oesophageal foreign body in children: 15 years experience in a tertiary care paediatric centre - Amit Singh; Minu Bajpai; Shashanka Shekhar Panda; Karunesh Chand; Manisha Jana; Abid Ali (Wolters Kluwer Medknow Publications, 2014)
Background: The objective of this study was to report our experience and outcome in the management of oesophageal foreign body (EFB) in suspected cases of foreign body (FB) ingestion. Materials and Methods: Records of children with documented EFB ingestion treated in the Department of Pediatric surgery from January 1997 to December 2012 were analysed. Diagnosis was made on the basis of history, clinical examination and radiological evaluation. Stronger index of suspicion was kept in cases of sudden onset of symptoms with an inappropriate history of FB ingestion. Results: A total of 317 children underwent emergency rigid oesophagoscopy for EFB. Out of these, 206 were males and 111 were females. The most common EFB found was coins in 209 (65.9%) cases, followed by food bolus obstruction in 54 (17%), metallic FB in 29 (9.1%), plastic FB in 21 (6.6%), and button batteries in 14 (4.4%) cases. The most common site of FB impaction was found to be cricopharynx in 291 (92%) cases. Conclusions: High index of suspicion should be kept for EFB in children who present with unavailable history of FB ingestion. The wait-and-watch policy in cases of FB oesophagus is not always the correct approach, especially when it presents as respiratory distress of sudden onset.